Recent advances in phage therapy against bacterial infection in poultry - Sieo, Chin Chin (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The health management of birds is an important aspect in poultry production. Under the intensive production system where the birds are stocked up in high density, infections can spread rapidly in the flock. One of the major and common infections is those caused by bacteria. Bacteria infections such as colibacillosis, salmonellosis, campylobacteriosis normally spread through the oral faecal route. Once infected, the growth performance of the chickens would be affected and in severe cases, mortality occurred. Antibiotics at sub-therapeutic level may reduce the risk of bacteria infections and lead to growth promotion. However, long term exposure to the antibiotics has led to the emergence of antibiotic resistance in bacteria, and of concern is the antibiotic resistance in zoonotic pathogens. The global apprehension on this issue has led to the ban of antibiotics usage in animal production. All growth-promoting antibiotics were banned in Sweden in 1986, while avoparcin and virginiamycin were banned in Denmark in 1995 and 1998, respectively. The European Union banned the use of avoparcin in 1997 and bacitracin, spiramycin, tylosin and virginiamycin in 1999 (Casewell et al., 2003). The removal of the antibiotics has been reported to cause adverse consequences on animal health and welfare, and the controls for bacteria infections have been a challenge to the farmers.